(untitled) (Actual Problems of Mind, 2019)
This paper aims to justify the thesis that the lack of a unifying «national project» in Ukrainian history writing (a national historical narrative) should be considered rather as an advantage of our country. Now we have a real chance to construct a historical narrative of cultural convergence. The colonial past, when Ukrainian territories were parts of several cultural regions, gave us not only negative experience but also positive experience of cultural interaction (convergence). Nowadays multinationality, multiculturalism and religious polyconfessionality constitute a significant advantage of an independent Ukrainian state because it coincides with the main global tendency to build the common multicultural global world based on the idea of human rights.